1989
DOI: 10.2214/ajr.152.2.429-a
|View full text |Cite
|
Sign up to set email alerts
|

CT and sonographic features of pseudomyxoma peritonei

Abstract: one of which has a well-defined rim. The latter was a large mucincontaining cyst arising from right ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…[10][11][12][13] Computed tomography shows four basic patterns: (1) posterior displacement of the intestines with numerous low density masses and calcifications; (2) diffuse peritoneal infiltration appearing similar to ascites with septated fluid pockets filling the peritoneal cavity; (3) intrahepatic low density attenuated lesions 10 ; and (4) scalloping of intra-abdominal organs due to extrinsic pressure of adjacent peritoneal implants. Scalloping of the liver has been widely described but in 1987, Parikh et al reported the first case of splenic scalloping in pseudomyxoma peritonei.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Computed tomography shows four basic patterns: (1) posterior displacement of the intestines with numerous low density masses and calcifications; (2) diffuse peritoneal infiltration appearing similar to ascites with septated fluid pockets filling the peritoneal cavity; (3) intrahepatic low density attenuated lesions 10 ; and (4) scalloping of intra-abdominal organs due to extrinsic pressure of adjacent peritoneal implants. Scalloping of the liver has been widely described but in 1987, Parikh et al reported the first case of splenic scalloping in pseudomyxoma peritonei.…”
Section: Discussionmentioning
confidence: 99%
“…The use of radiological investigations is beneficial for the diagnosis of these conditions The routine investigations for ascites, which include serum biochemical profile and tumor markers, in addition to an initial radiological investigation with USG Abdomen will always help to point the diagnosis. 7,8 In this case, the only positive finding that led to the diagnosis was the initial suspicion on ultrasonography. Moreover, CT abdomen increased the suspicion and gave the impression of presence of the primary tumor in the appendix and cecum.…”
Section: Discussionmentioning
confidence: 81%